Effects of live versus heat-killed probiotics on acute diarrhea in young children - Atik Indriyani; Mohammad Juffrie; Amalia Setyati (Indonesian Pediatric Society, 2012)
Background Diarrhea remains one of the major causes ofmorbidity and mortality in children in developing countries.Probiotics have been shown to be beneficial for decreasing thefrequency and duration of diarrhea. However, the reported effectson reducing the duration of diarrhea have been varied.Objective To compare the effectiveness of live and heatô€‚killedprobiotics in 6ô€‚60 monthô€‚old children with acute diarrhea fordecreasing duration and frequency of diarrhea and improvingweight gain.Methods We conducted a randomized, singleô€‚blind, controlledtrial in children aged 6ô€‚60 months with acute diarrhea. Childrenwere randomized into two groups, receiving either live or heatô€‚killed probiotics. All children received standard treatment fordiarrhea and probiotics as adjuvant treatment. The primaryoutcomes were duration and frequency of diarrhea, as well asweight gain. Tô€‚test was used for data analysis.Results There were 165 children with acute diarrhea enrolledin this study. They were divided into 2 groups, with 83 childrenreceiving live probiotics and 82 children receiving heatô€‚killedprobiotics. There were no significant differences in diarrhealduration in the two groups. The mean durations of diarrhea inthe live and heatô€‚killed probiotic groups were 3.64 (SD 0.85) daysand 3.74 (SD 0.73) days (P>0.05), respectively. Mean diarrhealfrequencies were also not significantly different, with 3.25 (SD1.44) times per day in the live probiotic group and 3.26 (SD 1.20)times per day in the heatô€‚killed probiotic group (P>0.05). Inaddition, mean weight gain was not significantly different, 'With241.57 (SD 75.84) g in the live prohiotic group and 221.95 (SD85.38) g in the heat-killed prohiotic group (P>0.05).Conclusion There were no significant differences between live andheatô€‚killed probiotics for reducing duration and frequency of diarrhea,as well as in weight gain in children aged 6ô€‚60 months 'With acutediarrhea. [paediatr lndones. 2012;52:249-54].